PENILAIAN KINERJA SAHAM YANG MEMBENTUK PORTOFOLIO BERDASAR PREDIKSI VARIABEL FUNDAMENTAL (Studi Saham – saham Perusahaan Manufaktur Yang Terdaftar di BEI Tahun 2004-2008) - Utami, Yuni (PERMANA, 2011)
Portfolio in capital market context resembles financial assets of combination of several shares invested by investor in order to obtain optimal return with a minimum risk. The general load of  minimum risk in portfolio each securities for return are not perfect and positive correlation (Jogiyanto, 2000 : 143). The selected shares are shares with ultimate performance or out perform. One of the mathematics model employed to obtain out perform shares is by fundamental financial variable prediction. The aim of study is to acquire empirical from the performace of each share that can be positively predicted by fundamental variable, and to measure how big is the influence of each variable. Population in this study are manufacture sharres listed at BEI during 2004 – 2008 for as much as 149 company. Sample for this study are 117 selected company from population. Research data is obtained at Capital Market Directory and Consolidated Statements of Cash Flow. The entire model in this research is analyzed using logistic regression. The technique shows  that  the only variable  that can predict an out perform  share is Earning Per Share (EPS),  variable. It has profitability level of 0,074 and significance level  at α 10%. However, the remain three variable such as Closing Price, Return On Assets (ROA) and Cash Flow have Profitability levels of 0,739; 0,474; and 0,663 respectively are not significant at α 10%, thus can not predict and out perform share. From classification matrix with 50% cut off this model can result overall classification  value of  83,8%, which shows that the model is acceptable. Keyword : performance share, portfolio, fundamental financial variable